Pengaruh Citra Perusahaan, Kepercayaan, Dan Word Of Mouth Terhadap Kepuasan Pelanggan Pada PT Grab Teknologi Indonesia - Afra Afifah; Saefudin Zuhdi (Jurnal Ilmiah Manajemen Kesatuan, 2022)
This research was conducted to find out the influence of corporate image, trust ,and word of mouth on customer satisfaction at PT Grab Teknologi Indonesia which was tested simultaneously and partially. Researchers used people who use Grab in the city of Bogor as respondents, the number of samples in this study was 160 people, using Hair et al. Data collection techniques using questionnaires that have been tested for validity and reliability. This study uses quantitative descriptive methods and the analysis used is multiple linear regression analysis using SPSS Version 25. The results show that partially: Corporate Image and Word of Mouth have a significant effect on customer satisfaction, this is evidenced by the value of t count > t table (4,227 and 6,951 > 1,978) and a significance value of 0.000 (sig <0.05), while the Trust variable has no significant effect. This is evidenced by the value of t count < t table (1.112 < 1.978 ) and a significance value of 0.264 (sig <0.05). Simultaneously Company Image, Trust, and Word of Mouth have a significant influence simultaneously on Customer Satisfaction in PT Grab Teknologi Indonesia. This is evidenced by the significant value of 0.000 <0.05 and the calculated F value of 84,483 > F table 0.266. In the coefficient of determination test, the influence of the variable Corporate Image, Trust, and Word of Mouth on Customer Satisfaction shows a value of 0.619 or equal to 61.9%. This figure implies that the variables of Corporate Image, Trust, and Word of Mouth simultaneously (together) affect the Customer Satisfaction variability by 61.9%. While the rest (100% - 61.9 = 38.1) is influenced by other variables outside the regression equation or variables not examined Key Word : Company Image, Trust, Word of Mouth, Customer Satisfaction